Comparison of the In Vitro and Ex Vivo Permeation of Existing Topical Formulations Used in the Treatment of Facial Angiofibroma and Characterization of the Variations Observed - Guillaume Le Guyader; Bernard Do; Victoire Vieillard; Karine Andrieux; Muriel Paul (MDPI AG, 2020)
Rapamycin has been used topically to treat facial angiofibromas associated with tuberous sclerosis for more than a decade. In the absence of a commercial form, a large number of formulations have been clinically tested. However, given the great heterogeneity of these studies, particularly with regard to the response criteria, it was difficult to know the impact and thus to compare the relevance of the formulations used. The objective of this work was therefore to evaluate the link between the diffusion of rapamycin and the physico-chemical characteristics of these different formulations on Strat-M® membranes as well as on human skin using Franz cells. Our results underline the importance of the type of vehicle used (hydrogel > cream > lipophilic ointment), the soluble state of rapamycin and its concentration close to saturation to ensure maximum thermodynamic activity. Thus, this is the first time that a comparative study of the different rapamycin formulations identified in the literature for the management of facial angiofibromas has been carried out using a pharmaceutical and biopharmaceutical approach. It highlights the important parameters to be considered in the development and optimization of topical rapamycin formulations with regard to cutaneous absorption for clinical efficacy.